Repenting for Antisemitism: “To Elevate Evil into a State of Goodness” - Von Kellenbach, Katharina (Studies in Christian-Jewish Relations, 2021)
This article explains the benefits of repentance over reconciliation especially in the context of enduring ideologies of contempt and habits of supremacy, such as Christian Jew-hatred. In the second part, the theological proposals of two theological associations, the Christian Scholars Group and the Society of Post-Supersessionist Theology, which were founded to repent for theological anti-Judaism, are examined. Using Paul’s covenantal metaphor of the olive tree in Romans 11, the author evaluates different covenantal proposals to overcome supersessionism in light of the biology of grafting.